2003
DOI: 10.1300/j076v37n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Severely Mentally Ill Inmates: Can Small Jails Comply with Detection Standards?

Abstract: Most researchers conclude that from six to fifteen percent of jail detainees meet the diagnostic criteria for severe mental illnesses including schizophrenia, bipolar disorder, and major depressive disorder. Although legal and professional standards mandate screening for mental illness in jails, few procedures exist that can be completed within the limited time constraints under which jails function. This study compares the detection rates of the Referral Decision Scale with a short, officer-administered booki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Most research to date seems to suggest that traditional jail booking procedures are insufficient and existing tools have limited predictive accuracy. McLearen and Ryba (2003) reported the prisoner intake procedure in a mid-western county jail in the U.S. detected slightly less than half of the inmates diagnosed with a severe mental illness. Similarly, Birmingham, Gray, Mason, and Grubin (2000) found that one in four newly remanded men in a prison reception center in England had some form of mental illness and 3/4 of those disorders failed to get recognized by the institution's screening staff.…”
Section: Includes the Bprs-e) Compared To Independent Evaluations Of mentioning
confidence: 99%
“…Most research to date seems to suggest that traditional jail booking procedures are insufficient and existing tools have limited predictive accuracy. McLearen and Ryba (2003) reported the prisoner intake procedure in a mid-western county jail in the U.S. detected slightly less than half of the inmates diagnosed with a severe mental illness. Similarly, Birmingham, Gray, Mason, and Grubin (2000) found that one in four newly remanded men in a prison reception center in England had some form of mental illness and 3/4 of those disorders failed to get recognized by the institution's screening staff.…”
Section: Includes the Bprs-e) Compared To Independent Evaluations Of mentioning
confidence: 99%
“…Finding no elderly inmates in larger facilities seems unlikely so it is possible that the true population may be undercounted in some jails. McLearen and Ryba (2003) found that smaller jails report having fewer persons with severe mental illness. It is plausible that small jails are more likely to undercount the true rate of other special needs populations as well.…”
Section: Resultsmentioning
confidence: 98%
“…Common concerns with patient selection included sampling from populations with high rates of mental illness such as health care units and substance abuse programs [ 33 , 36 , 37 ], convenience sampling [ 32 , 38 , 39 ] and high refusal and/or drop-out rates [ 20 , 27 , 28 , 40 - 42 ]. In a number of studies [ 30 , 33 , 43 ] index tests were developed by statistically choosing a subset of items that performed best from a larger test battery, and in other studies [ 38 , 44 ], the index test was embedded within the diagnostic assessment.…”
Section: Resultsmentioning
confidence: 99%